Between Success and Failure: Integrating Agile Project Management Methods with PRINCE2 Framework for the Enhanced Management of Imperfect Projects - Savio, Rajesh (Eximia, 2022)
As most of the project fail in the developing world, a proper approach or framework is needed that can reduce the chances of project failure but increase the likelihood of success. One approach that can be used is integrating agile methodology and PRINCE2 framework, which have the benefits of minimizing project risks, aligning costs and time with the outcome, and guaranteeing the quality of the project results. This paper discusses a framework to manage imperfect projects properly.